(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
At remote locations where mobile networks are not present and remote sensing cannot provide enough information, an ad-hoc network with rechargeable nodes can be implemented. This paper discusses an ad-hoc network of camera based wireless intrusion detection system. In the proposed system each node has been implemented using a motion sensor, digital camera, transmission module, and solar-powered battery. Function of every node is to continuously monitor the occurrence of any intrusion in its range by using a motion detection sensor. The motion sensor triggers the digital camera only when the intrusion occurs. After triggering, camera gets switched on instantaneously and starts capturing the visual data. This recorded visual data is transmitted serially to the base station using Zigbee or Bluetooth transmission module. At the base station, the received information is decoded to obtain visual data. For keeping track of all nodes present in a network, the battery voltage level is also transmitted from each node to the base station at fixed time intervals. Various image parameters are calculated and the energy efficiency of the system is also evaluated at the base station. It is found that the wireless intrusion detection system presented in this paper is reliable and energy efficient.